Mapping Leadership Gaps in Indian HR Management: A Conceptual Review with Emphasis on Delhi/NCR (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This research paper explores the current state of Human Resource (HR) management in India, focusing particularly on the challenges and potential strategies for developing HR leadership within organizations situated in metropolitan business hubs such as Delhi and the National Capital Region (NCR). The research is grounded in an in-depth examination of secondary sources, which encompass government reports, industry white papers, published academic literature, and case studies from prominent Indian companies. It emphasizes the fact that, even though there has been an increasing level of awareness about the strategic significance of human resource (HR) operations, many businesses in India still do not have a codified framework in place to cultivate leaders in the field of human resources.There are a number of important sections into which the paper is separated. The conceptual framework for human resources (HR) leadership is presented in the introduction, and the significance of the subject is explained within the context of the quickly changing corporate landscape in India. The literature study compiles and analyzes the conclusions that have already been reached about human resource practices, management development frameworks, and leadership gaps in both India and other countries. The study is in accordance with pre-existing theories of leadership development and organizational behavior because of the theoretical framework.The parts that follow assess the existing gaps in leadership pipelines, the hurdles posed by organizational culture, and the geographical differences that impede the growth of human resources leadership in Indian companies. This talk provides an overview of how these problems impact the performance of an organization, the morale of its employees, the planning for future leadership, and the capacity to maintain operations over a long period of time. The necessity of making structural reforms and enhancing collaboration between academia, government, and the industry is acknowledged in the conclusion.The last section of the study offers concrete suggestions for creating HR development academies that are tailored to specific regions in Delhi/NCR, as well as advancing legislative support and developing leadership models that are based on competency.